(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, the non-linear Fractional order susceptible-infected-Recovered(SIR) mathematical model of computer viruses is presented. For this Fractional differential transform method (FDTM) and the Laplace-Adomian decomposition method (LADM) are applied and compared the obtained results with Runge-Kutta Felhberg Method for γ = 1. Also, graphs of solutions are plotted up to five iterations from both the method. The fractional derivative used in the model is Caputo Fractional derivative. Using Lyapunov stability analysis,the stability verified of the given mathematical model. Solutions are obtained for three different fractional order values of γ. The validity of the result is confirmed by converting model into integer order. Errors from both the methods are compared.